Marketing of Indian National Bibliographic Databases on Cd-rom to University and College Libraries and District and State Central Libraries: a Study - Meshok, John (Journal of Information and Knowledge, 2014)
The use of Indian National Bibliography by libraries, booksellers, publishers, readers and scholars increases day by day since it is an authoritative bibliographical record that keeps the users informed about the literary output of our nation. It is an essential reference tool for book selection. Marketing of INB database on CD-ROM, the only Electronic Information Product helps to enhance the quality of reference service with the use of modern computer technologies. INB is very much needed for the academic and public libraries since it is the only reliable book selection tool. There will be no competition in marketing the database because it is the only national bibliography published from Central Reference Library, Kolkata. The purpose of INB is to provide reference service to the librarians, publishing world, teaching professionals, scholars and research communities. The main objectives are to do the primary task of copying the database on CD-ROM and distribute the INB database to all universities and colleges libraries and all districts and state central libraries. And the authority should make sure to create security policies which bar downloading of the database and policies for enforcing the copyright act that prevent illegal copying. To promote the sale of product, giving advertisement about the institution with detailed web address and email address and collecting the addresses of all the abovementioned libraries and request them to subscribe to electronic database and its printed form through online subscription. There are some limitations in marketing INB database, since in electronic / digital library environment it makes the copyright production a difficult task. Production cost will increase when the work co copying the database on CD-ROM is given to private jobbers. Distribution of the product to all libraries is a very big task. It is suggested that this will be good if the CD-ROM database is prepared and sent half-yearly. The details of each new printed INB volume and its database on CD-ROM with price list should be regularly updated in the website. Marketing of the CD-ROM database, which will be available at a low price that can be affordable by any library, will be a successful one when the academic libraries and public libraries feel the values of INB and its need.